Framing Media Atas Pemberitaan Sertifikasi Dai - Abd Munib (Ar-Raniry State Islamic University, Indonesia, 2020)
The emergence of new preachers in addition to offering fresh air for people's understanding of Islam as well as being a challenge in itself because it can provide extreme understanding. As a result of religious messages conveyed by extremist preachers, people will be trapped in anti-tolerant actions so that they can threaten the nation and state. Based on this, the Indonesian Ulema Council (MUI) considers the need for a standardization policy in order to create enlightening lecturers. This event did not escape the spotlight of the media even the media have their own characteristics in framing standardization dai. Based on good data from syntax, thematic, rhetorical scripts from all three media: Tempo.co, Medcom.id, and BBC.com show that Tempo.co framed the importance of MUI policy in creating enlightening propagation such as